Exploring the components of bleeding outcomes in transfusion trials for patients with hematologic malignancy. Issue 1 (13th October 2020) - Balitsky, Amaris K.; Liu, Yang; Van der Meer, Pieter F.; Heddle, Nancy M.; Arnold, Donald M.
Background: Clinically significant bleeding in patients with hematologic malignancies is a heterogeneous composite outcome currently defined as World Health Organization (WHO) bleeding Grades 2, 3, and 4. However, the clinical significance of some minor bleeds categorized as WHO Grades 1 and 2 remains controversial. We analyzed the number and frequency of individual signs and symptoms of WHO Grades 1 and 2 bleeds and explored their association with more severe incident bleeds graded as WHO Grades 3 and 4. Study Design and Methods: We aggregated daily bleeding assessment data from three randomized controlled trials conducted in patients with hematologic malignancies that used bleeding as an outcome. Cox proportional hazard regression analysis was used to identify signs and symptoms categorized as WHO Grades 1 and 2 bleeds that were associated with more severe bleeds (Grades 3 and 4). Results: We collected data from 315 patients (n = 5476 daily bleeding assessments; 3383 [61.8%] with a bleed documented). A total of 98.3% (3326/3383) were Grade 1 and 2 bleeds and 1.7% (57/3383) were Grades 3 and 4. Grade 1 and 2 bleeds were composed of 20 different bleeding signs and symptoms. Hematuria (hazard ratio, 16.1; 95% confidence interval, 4.4‐59.2; P < .0001) was associated with incident Grade 3 or 4 bleeds. Conclusion: In patients with hematologic malignancy, only hematuria (microscopic and/or macroscopic) was associated with more severe incident bleeds. This findings require validation in independent data sets. Abstract : Link to: Editorial TRF16277